L’informatique, mot nouveau et art relativement récent - Parizeau, Gérard (Assurances)

(untitled) (HEC Montréal, 1981)
Electronic processing is a new and complex art. The computer has become a very valuable working tool with great possibilities. In the following article, the author deals not only with the extraordinary services rendered by the computer but also with certain weaknesses that even the cleverest technicians have been unable to correct. Mr. Parizeau acquaints us with the numerous studies which have been presented by specialists associated with the Sodarcan Group and others who have been instrumental in simultaneously aiding us to demystify computer systems and to demonstrate to us the economic import thereof.